Partially fluorinated tetraazaacenes by nucleophilic aromatic substitution - Engelhart, Jens U.; Lindner, Benjamin; Tverskoy, Olena; Rominger, Frank; Bunz, Uwe H. F. (The journal of organic chemistry, 2013)
We report the sodium hydride-mediated reactions of a diethynylated diaminophenazine with perfluorobenzene, perfluoronaphthalene, and two octafluoroanthracene derivatives. In all of the cases, an N,N-dihydropyrazine ring is formed, and partially fluorinated tetraazapentacenes, tetraazahexacenes, and tetraazaheptacenes (in their respective N,N-dihydro forms) are easily prepared. In the case of the dihydrotetraazapentacenes and -hexacenes, oxidation with manganese dioxide is possible to give the desired, fully unsaturated tetraazaacenes; two molecules of the azahexacene undergo a Diels-Alder reaction in which an alkyne substituent in the conserved hexacene unit works as the dienophile while the tetraazahexacene participates as the diene to give an unsymmetrical dimer. All of the coupling targets were investigated by NMR and UV-vis spectroscopies, and several single-crystal structures of the N,N-dihydrotetraazaacenes and also that of the tetrafluorotetraazaacene were obtained.